Hubungan Karakteristik Sosiodemografi Terhadap Tingkat Kepuasan Pelayanan Kefarmasian di Apotek X Kota Sorong - Diah Wulandari; Angga Bayu Budiyanto; Lukman Hardia (Jurnal Ners, 2026)
This study aims to determine the relationship between patient sociodemographic factors (age, gender, education, occupation, income,and travel distance) with satisfaction with pharmaceutical services at Pharmacy X, Sorong City. This study used a quantitative observational approach with a cross-sectional design and involved 181 respondents selected through a total sampling technique inthe period September - October 2025. Data collection was carried out using a questionnaire that had passed validity and reliability tests, and then analyzed using the chi-square. The results of the analysis showed that the variables of gender, age, education, occupation, and travel distance did not show a significant relationship with the level of satisfaction with pharmaceutical services (p> 0.05). Meanwhile, the income variable showed an important relationship with the level of satisfaction (p = 0.01). Overall, the levelof patient satisfaction on the five dimensions of Servqual was in the very satisfied category, especially on the dimensions of appearance, attention, and assurance. These findings illustrate that the quality of pharmaceutical services at Pharmacy X, SorongCity, is already very good, but there are differences in perceptions of satisfaction among patients with different income levels. Theresults of this study are expected to provide input for pharmacies to continuously improve service quality